(untitled) (Research, Society and Development, 2021)
In public administration, the management of projects of municipal interest must seek the optimization of human resources to enable time reduction in the stages of evaluation and monitoring of project activities. The purpose of this article is to present the benefits that were acquired with the implementation of an adaptation of the Scrum framework in the Project Management (PM) sector of the Municipal Public Works and Urban Services – SEMOP, in the county of Santana (AP). As a result, it was possible to standardize the elaboration of architectural projects and their complementary ones and, at the same time, manage them, indicating that the Scrum framework is not restricted to software engineering projects. When well used, this tool improves relationship teams, facilitates monitoring and development of any project, reduces materials waste, and elaborates time, besides promoting constant maintenance of the organization’s good practices and disseminating the tactical knowledge of those involved in teams participating projects. During the tool analysis time, an average of 66% was optimized in the time previously allocated to the evaluation and approval activities of projects at SEMOP. However, despite the positive results regarding the economy of resources, it is still necessary to hire new servers and purchase equipment to help them perform their daily work to prepare projects.